Factors associated with the intention of consumption of native food in students of a peruvian university - Soria Mendo, Carmen Oly Elisa (2021)
The objective of this study was to identify the factors associated with the intention to consume native foods in students of the Universidad Nacional Agraria La Molina, during the 2019-II semester, in the city of Lima. The survey technique was used and the questionnaire was used as a collection instrument. 177 valid surveys were collected through a probability cluster sampling. Two statistical tests were applied: Pearson’s Chi Square Test and Spearman’s Correlation Test. In both tests, a statistically significant association was found between the variable intention to consume native foods and the variables: attitude, subjective norm and perceived control over the consumption of the aforementioned foods. It is concluded that the intention to consume native foods at the La Molina National Agrarian University is related to the attitude, the subjective norm and the perceived control over performing said behavior.